Evaluation of heavy metal sorption capacities of cellulose based adsorbents with ionic functional groups – aqueous cobalt (II) ion removal - ŞAM, SERDAR; HACIOSMANOĞLU, GÜL GÜLENAY; CAN, ZEHRA SEMRA (My University, 2022)
This study focuses on developing a novel foam material with ionic functional groups using the most abundant natural resource, cellulose, for the removal of heavy metals. Ionic functionalities were introduced to cellulose-based foam for increased affinity towards heavy metals. Based on the type of cellulose polymer used in the synthesis, four different cellulose based foam material batches were obtained, these are, activated cellulose, cellulose acetate, carboxymethyl cellulose, and acetylated carboxymethyl cellulose based foam materials. Heavy metal removal capacity of each foam material was tested using cobalt as the model heavy metal. At pH of 6.5, foam dose of 10 g/L, and initial Co2+ concentration of 100 mg/L, heavy metal removal capacities of the foam samples varied between 2% to 36 %, while foam material produced by cellulose acetate revealed the highest removal efficiency, 36%. Co2+ removal efficiency of cellulose acetate based foam increased to 50% when 15 g/L of foam sample was used under otherwise the same experimental conditions. Adsorption behavior of the cellulose acetate based foam material was also studied, which suggested Sips isotherm model as the most suitable adsorption mechanism.
Keywords: Çevre Mühendisliği; Çevre Teknolojisi; Su Kirliliği ve Kontrolü; Mühendislik ve Teknoloji; Environmental Engineering; Environmental Technology; Water Pollution and Control; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Çevre / Ekoloji; SU KAYNAKLARI; ÇEVRE BİLİMLERİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); ENVIRONMENT/ECOLOGY; WATER RESOURCES; ENVIRONMENTAL SCIENCES; Su Bilimi ve Teknolojisi; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Water Science and Technology; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; heavy metal removal; cellulose; adsorption; cobalt; isotherm